High-stakes reform : the politics of educational accountability - McDermott, Kathryn A., 1969- (Public management and change., 2011)
Performance accountability has been the dominant trend in education policy reform since the 1970s. State and federal policies set standards for what students should learn; require students to take "high-stakes" tests to measure what they have learned; and then hold students, schools, and school districts accountable for their performance. The goal of these policies is to push public school districts to ensure that all students reach a common threshold of knowledge and skills. High-Stakes Reform analyzes the political processes and historical context that led to the enactment of state.